IMPLEMENTATION OF EOQ AND ROP METHODS IN WEB-BASED INVENTORY MANAGEMENT AT CV KALIREJO MAKMUR - fiki Marzuqi; Supriyono; Diana Laily Fithri (LPPM Universitas Abdurrab, 2026)
CV Kalirejo Makmur is a distribution and trading company with several branch stores and a central warehouse for storing goods before distribution. Currently, the company faces challenges in inventory management, particularly in the process of requesting goods from branches, which is still conducted manually via WhatsApp. This condition leads to inefficiencies, delivery delays, recording errors, and difficulties in monitoring and reconciling stock data, resulting in overstock or understock situations that increase storage costs and disrupt distribution operations. The lack of an integrated system and real-time stock visibility also hinders management in making accurate decisions. To address these issues, the implementation of the Economic Order Quantity (EOQ) and Reorder Point (ROP) methods is proposed as a strategic solution to optimize order quantities and improve inventory control. The EOQ and ROP based inventory management information system was developed using the PHP programming language and MySQL database with a responsive web-based interface. The implementation results show that the system generates an optimal order quantity recommendation of 3,435 units and a reorder point of 281 units, which can be used as a reference for procurement and replenishment decisions. These results indicate that the system is capable of reducing the risk of overstock and understock, improving inventory management accuracy, accelerating distribution processes, and supporting effective data-driven decision making.